Learning history through project-based learning - Sin Wei Lim; Rosmawijah Jawawi; Jainatul Halida Jaidin; Roslinawati Roslan (Journal of Education and Learning (EduLearn), 2023)
In a 21st century classroom, project-based learning (PBL) can be the key strategy in helping students become independent learners and thinkers. PBL provides a pedagogical approach that is appealing and can be used not only in the subject of history but also across different disciplines. This study examines the impact of project-based learning on students’ understandings of Upper Secondary Brunei history lessons. Data was collected from a Year 10 Upper Secondary history classroom in one secondary school in Brunei through an action research method. The instruments used were lesson observations, semi-structured interviews and pre- and post-tests. The interview was conducted with eight students while classroom teaching of the subject teacher was observed. The pre- and post-tests were given to students before and after the intervention of PBL. The findings in this study showed that the students were still underperforming after the PBL intervention but had shown potential for further improvements with more exposure to project-based learning.